Saudi Arabia celebrates women's achievements on National Day | السعودية تحتفل بإنجازات المرأة تزامنا مع اليوم الوطني - Publishing and Public Relation Department | إدارة النشر والعلاقات العامة (2024)
In recent years, Saudi women have made progress in various fields, becoming more effective in building the society of the Kingdom, which celebrates its 92nd National Day on Friday.